Sclerotium rolfsii에 의한 양파 흰비단병 - 권진혁(Jin-Hyeuk Kwon); 김희대(Hee-Dae Kim); 최옥희(Okhee Choi); 곽연식(Youn-Sig Kwak); 이용환(Yong Hwan Lee); 심홍식(Hong-Sik Shim) (Sigmulbyeong yeon'gu, 2011)
The sclerotium rot of onion (Allium cepa L.) was occurred sporadically in the farmer's fields at Daehap, Changnyeong in Korea. The typical symptom was water-soaking on the bulb, stem and leaves and then rotting, wilting, blighting and the infected plants eventually were rotted and died. The sclerotia were globoid, 1-3 mm, and white to brown. The optimum temperature for mycelial growth and sclerotial formation on PDA was $30^{°}C$. The hyphal width was 4-9 ${μ}m$. The typical clamp connections were observed in the hyphae of the fungus grown on PDA. On the basis of mycological characteristics, ITS rDNA sequence analysis, and pathogenicity, this fungus was identified as Sclerotium rolfsii Saccardo. To our knowledges, this is the first report of sclerotium rot on onion caused by S. rolfsii in Korea. 경남 창녕군 대합면 양파 재배농가 포장에서 Sclerotium rolfsii에 의한 양파 흰비단병 증상이 발생되었다. 병징은 인경과 줄기 및 잎이 수침상으로 물러지고 썩으면서 시들어 말라 죽고, 병반부와 지제부의 토양 표면에 흰색의 곰팡이가 발생하며 갈색의 작고 둥근 균핵을 형성하였다. 감자한천배지에서 균총은 흰색이며 배양기간이 경과됨에 따라 갈색의 작고 둥근 균핵을 많이 형성하였다. 균핵의 크기는 1-3 mm이며 균사의 폭은 4-9 ${μ}m$였다. 균사생육과 균핵 형성 적온은 $30^{°}C$었다. 균사특유의 clamp connection이 관찰되었다. 양파에서 발생한 병징과 병원균의 균학적 특징, 그리고 ITS rDNA 염기서열 비교분석 결과, 이 병을 S. rolfsii에 의한 양파 흰비단병으로 명명하고자 제안한다.